Patients With Type 2 Diabetes Mellitus and Heart Failure Benefit More From Sodium-Glucose Cotransporter 2 Inhibitor: A Systematic Review and Meta-Analysis - Chen, Chengcong; Peng, Hong; Li, Mingzhu; Lu, Xiyan; Huang, Miao; Zeng, Yongmei; Dong, Guoqing (Frontiers in Endocrinology, 2021)
Background: Patients with type 2 diabetes mellitus (T2DM) and heart failure (HF) are at higher risk of mortality and hospitalization for heart failure (HHF). A recent study showed that sodium-glucose cotransporter 2 (SGLT-2) inhibitors may be a promising choice. Methods: We searched the PubMed, Embase, and Cochrane databases of clinical trials for randomized controlled trials investigating the long-term effects of SGLT-2 inhibitors in patients with T2DM and HF compared with placebo. The primary outcome was cardiovascular death or HHF, and the secondary outcomes included cardiovascular death (CV death), HHF, and all-cause mortality. We also conducted an exploratory analysis and tried to identify the population, which will benefit more from the treatment. Results: After the study selection, a total of 5 trials, including 4 subgroup analyses, met the eligibility criteria. The results suggested that the use of SGLT-2 inhibitors was associated with a reduction in the incidence of CV death or HHF (HR, 0.69[95%CI, 0.63-0.77], P＜0.00001), CV death (HR, 0.80[95%CI, 0.69-0.92], P = 0.001), HHF (HR, 0.67[95%CI, 0.60-0.76], P < 0.00001), and all-cause mortality (HR, 0.74[95%CI, 0.64-0.86], P < 0.0001). Moreover, patients with T2DM and HF may benefit more from the treatment than those with T2DM/HF. Conclusion: The long-term use of SGLT-2 inhibitors can help reduce the risk of mortality and HHF in patients with T2DM and HF.